Iron-confined hierarchically porous biochar: Efficient BPA degradation via free radical/non-radical mechanisms from multiple active sites - Jiahui Wen; Liang Zeng; Yating Long; Mengwu Xiao; Zhiqiang Huang; Manxia Lu; Zuowei Xiao; Sihan Lu; Xi Chen; Lanqing Deng (Environmental Research, 2026)

Subcellular-scale directed green synthesis of nanoparticles: First insight into protein-level regulatory mechanisms of electron donors on palladium nanoparticle biosynthesis pathways in Bacillus megaterium Y-4 - Yating Jia; Jing Lu; Yongfen Long; Bin Hou; Yuancai Chen (Journal of Environmental Chemical Engineering, 2025)

Effects of low-density polyethylene microplastics on soil functions and microbial communities across soil depths - Jing Lu; Yongfen Long; Bin Hou; Xuetao Guo; Yu Zhang; Hongjuan Bai; Yating Jia (European Journal of Soil Biology, 2025)

Allicin fumigation delays the decline of fruit quality in blueberries via regulation of reactive oxygen species - Siyu Long; Bo Xu; Yating Zhang; Yingchao Qu; Shujuan Ji; Manli Luo; Meilin Li; Bing Bai; Qian Zhou (Postharvest Biology and Technology, 2025)

Bimetallic CuFe2O4 photocatalytic activates persistent free radicals and accelerates electron transfer in biochar: Efficient degradation of tetracycline - Jiahui Wen; Yating Long; Liangdi Zhu; Liang Zeng; Xu Qin; Sirong Song; Manxia Lu; Lanqing Deng (Environmental Research, 2025)

Response of soil organic carbon to land-use change after farmland abandonment in the karst desertification control - Yating Mu; Runcheng Ye; Kangning Xiong; Yue Li; Ziqi Liu; Yidong Long; Lulu Cai; Qingping Zhou (Plant and Soil, 2024)

Pathways and contributions of sulfate reducing-bacteria to arsenic cycling in landfills - Lifang Hu; Feng Huang; Yating Qian; Tao Ding; Yuzhou Yang; Dongsheng Shen; Yuyang Long (Journal of Hazardous Materials, 2024)

High nutrient availability modulates photosynthetic performance and biochemical components of the economically important marine macroalga Kappaphycus alvarezii (Rhodophyta) in response to ocean acidification - Chao Long; Yating Zhang; Zhangliang Wei; Lijuan Long (Marine Environmental Research, 2024)

Recent advance in high-intensity ultrasound modification of blue food protein: Mechanisms, functional properties and structural alterations - Zhihui Yu; Yating Gao; Xinyi Jia; Shuai Cui; Li Ma; Dan Zheng; Xin Li; Long Li; Lixin Zhang; Yisheng Chen (Trends in Food Science & Technology, 2024)

Remediation of heavy-metal-contaminated soil with two organic acids: Washing efficiency, recovery performance, and benefit analysis - Zilin He; Lulu Long; Han Yuan; Han Pang; Yating Wang; Liang Ye; Min Xu; Chao Chen; Yan Liu; Yinlong Xiao; Changlian Xu; Jun Wu; et al. (Journal of Cleaner Production, 2023)

Design and fabrication of anthocyanin functionalized layered clay/poly(vinyl alcohol) coatings on poly(lactic acid) film for active food packaging - Long Mao; Chengyu Wang; Jin Yao; Yating Lin; Xinxin Liao; Jing Lu (Food Packaging and Shelf Life, 2023)

Oxalic acid enhances bioremediation of Cr(VI) contaminated soil using Penicillium oxalicum SL2 - Bibo Long; Lingling Liao; Fei Jia; Yating Luo; Junyu He; Wenhua Zhang; Jiyan Shi (Chemosphere, 2023)

Increased light availability enhances tolerance against ocean acidification-related stress in the calcifying macroalga Halimeda opuntia - Zhangliang Wei; Yating Zhang; Fangfang Yang; Lijuan Long (Acta Oceanologica Sinica, 2022)

Diurnal fluctuations in seawater pCO2 amplify the negative effects of ocean acidification on the biotic performance of the calcifying macroalga Halimeda opuntia - Zhangliang Wei; Yating Zhang; Fangfang Yang; Lijuan Long (Frontiers in Marine Science, 2022)
Although the adverse effects of increasing atmospheric CO 2 -induced ocean acidification (OA) on marine calcifying macroalgae have been widely reported, there are limited studies on how daily fluctuations in p CO 2 (pH) within shallow ecosystems influence the growth and physiological performance of these calcifiers. Therefore, a 42-day laboratory mimetic experiment to determine how growth, biological performance and related carbon and nitrogen metabolic products of the calcifying macroalga, Halimeda opuntia are generated in response to fluctuating p CO 2 under OA conditions (1200 ppmv) was performed. The results of present study showed that the adverse effects of OA were more determined by the adverse influence of elevated acidity (H + ) on growth rates, calcification, photosynthesis and the related biotic performance of H. opuntia compared with the positive effects that higher CO 2 provided. Moreover, diurnal fluctuations in p CO 2 levels [with higher (nearly 8.10) and lower pH (nearly 7.40) values during day and night times, respectively] have amplified these negative influences on H. opuntia . To mitigate elevated p CO 2 -related stress, higher contents of free amino acids and proline were highly secreted and likely linked to protecting the integrity of algal cellular structures. The above results contribute to increasing our understanding of the biological consequences of p CO 2 (pH) variability on calcifying Halimeda species and their physiological plasticity in response to further oceanic p CO 2 changes.